Preparation method and application of metal organic framework ZIF-8 / polyimide foam material
通过将ZIF-8与聚酰亚胺泡沫材料进行复合,制备出ZIF-8/PI泡沫复合材料,解决了ZIF-8粉体在水中分散性高、回收损耗大的问题,实现了高效的水合 The effect of physical generation and fast gas storage.
Patent Information
- Application Number
- CN202310480738.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-04-28
AI Technical Summary
In the prior art, when ZIF-8 is used as a hydrate promoter, the powder form is directly dispersed in the aqueous phase, and a sufficient gas-liquid contact surface cannot be formed, which limits its application effect. In addition, ZIF-8 particles at the nanoscale are in water. It has high dispersion, resulting in huge recovery losses and high operating costs.
By compounding the precursor solution of the polyanide foam material with the metal organic skeleton ZIF-8, the ZIF-8/Pi foam composite material is prepared, and the vacuum frozen drying method is used to load the ZIF-8 on the surface of the polylide foam. Form a multi -level hole structure to improve the contact surface and recycling of the gas fluid.
The efficient recycling and utilization of the ZIF-8 is realized, enhanced the reaction venue and gas transmission of hydrophilic objects, promoted the rapid generation of natural gas hydrochties, reduced operating costs, and increased the gas storage multiple.
Smart Images

Figure CN116478444B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam materials, and in particular to a preparation method and application of a metal organic framework ZIF-8 / polyimide foam material. Background Art
[0002] Due to its mild storage conditions, solid natural gas technology based on hydrates has received extensive attention in the field of natural gas storage and transportation, and is considered to be a new generation of natural gas storage alternative technology. However, the slow hydrate nucleation and growth kinetics and low gas storage capacity have limited the application and promotion of this technology to a certain extent.
[0003] Considering the huge specific surface area and abundant pores of nanoporous materials, introducing them into the hydrate reaction system can greatly improve the nucleation and growth rate of hydrates. It is reported that the addition of materials such as carbon nanotubes and metal organic frameworks (MOF) can greatly shorten or even eliminate the hydrate induction period and increase the hydrate growth rate. These nanoporous materials use their excellent adsorption properties to increase the amount of gas dissolved in the reaction system. At the same time, the faster gas adsorption rate can provide abundant gas sources for the main water phase to improve the hydration conversion rate, thereby realizing an efficient "adsorption-hydration" gas storage system.
[0004] As an emerging MOF material, ZIF-8 is a powdery substance with a rich microporous structure. The metal atoms can provide strong adsorption sites for gases. It has important applications in gas adsorption and separation. These advantages also lay a good foundation for its application in adsorption-hydration gas storage technology.
[0005] However, when ZIF-8 is used as a hydrate promoter, it is mostly directly dispersed in the water phase in the form of powder, and it is unable to form a sufficient gas-liquid contact surface, which greatly limits its application effect. At the same time, nanoscale ZIF-8 particles have high dispersibility in water. After a reaction, they need to be recovered by filtration, centrifugation and other methods, and the loss in the process is huge, and the operating cost is extremely high. In addition, the nanopore structure of ZIF-8 is of a single scale, and it is impossible to construct a multi-scale reaction site for hydrate formation, and it is impossible to achieve an ideal hydrate phase equilibrium effect. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a preparation method and application of a metal organic framework ZIF-8 / polyimide foam material.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] On the one hand, the present invention provides a method for preparing a metal organic framework ZIF-8 / polyimide foam material, which is characterized by: using a polyimide foam material and a precursor solution of a metal organic framework ZIF-8 as raw materials, extracting gas from the polyimide foam material, then absorbing the precursor solution of the metal organic framework ZIF-8 to saturation, taking it out after standing for reaction, washing it with deionized water, and vacuum freeze-drying it to obtain a metal organic framework ZIF-8 / polyimide foam material, that is, a ZIF-8 / PI foam composite material;
[0009] The amount or concentration of the ZIF-8 precursor solution is controlled so that the mass ratio of ZIF-8 to PI in the final foam material is 1-2.5:1.
[0010] Further:
[0011] The preparation process of the polyimide foam material is as follows:
[0012] 1) dissolving 3,3',4,4'-benzophenone tetracarboxylic dianhydride in a solvent, adding alcohol thereto, heating and stirring, carrying out esterification reaction to obtain a carboxylate solution, and naturally cooling to room temperature to obtain a solution A;
[0013] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B;
[0014] 2) Solution A and solution B are mixed, water is added and stirred, and then poured into a mold for foaming, and then high-temperature curing is performed to obtain a polyimide foam material.
[0015] The preparation process of the precursor solution of the metal organic framework ZIF-8 is as follows:
[0016] Weigh zinc nitrate hexahydrate and dissolve it in a solvent, which is recorded as solution C; weigh 2-methylimidazole and dissolve it in a solvent, which is recorded as solution D; wherein the mass ratio of 2-methylimidazole to zinc nitrate hexahydrate is 1.1:1.
[0017] The C solution is quickly poured into the D solution, and the mixture is stirred to obtain a precursor solution of the metal organic framework ZIF-8.
[0018] The composite process of the metal organic framework ZIF-8 and polyimide foam is as follows:
[0019] The polyimide foam is placed in a precursor solution of the metal organic framework ZIF-8. The gas in the foam is discharged by vacuuming and the precursor solution of ZIF-8 is absorbed. After being allowed to react at room temperature for 24 hours, the foam is taken out, repeatedly soaked and washed in deionized water, and then vacuum freeze-dried to obtain a ZIF-8 / PI foam composite material.
[0020] Furthermore, in step 1), the solvent is N,N-dimethylformamide, and the alcohol is methanol; the mass ratio of the solvent to 3,3',4,4'-dibenzophenone tetracarboxylic acid dianhydride is 4:3-5:3; the molar ratio of 3,3',4,4'-dibenzophenone tetracarboxylic acid dianhydride to alcohol is 1:2-1.2:2; the esterification reaction temperature is 60-70°C, and the esterification reaction time is 2-3h; the weight proportions of the components in solution B are: 40-50 parts of polyethylene glycol, 40-50 parts of water-soluble silicone oil, 1-5 parts of dibutyltin dilaurate, 10-20 parts of triethanolamine, and 280-300 parts of isocyanate.
[0021] Furthermore, in step 2), the mass ratio of solution A to solution B is 2:1-3:1; the mass ratio of added water to isocyanate is 1:2-1:1; the high temperature curing temperature is 180-240°C, and the curing time is 3-5h; the solvents of solution C and solution D are both methanol.
[0022] On the other hand, the present invention provides an application of the metal organic framework ZIF-8 / polyimide foam material, characterized in that it is used for the rapid generation of natural gas hydrates, the steps are:
[0023] 1) extracting gas from the ZIF-8 / PI foam composite material, then absorbing water until saturated, and taking out the ZIF-8 / PI foam composite material;
[0024] 2) placing the water-absorbed ZIF-8 / PI foam composite material into a high-pressure methane reactor, sealing it and placing it in a low-temperature constant temperature bath;
[0025] 3) When the temperature is constant at 1°C ± 0.2°C, open the methane cylinder to inflate the high-pressure reactor. After completion, close the methane cylinder, the hydrate reaction begins, and natural gas hydrate is generated.
[0026] The beneficial effects of the present invention are:
[0027] (1) The present invention creatively combines metal organic framework ZIF-8 with PI foam. On the one hand, a ZIF-8 / PI composite foam material with a molded structure is prepared, which improves the recyclability of ZIP-8. At the same time, the three-dimensional macroscopic structure of polyimide foam ensures the high dispersibility of ZIF-8 in water. On the other hand, through the composite of the two in a specific ratio, the ZIF-8 / PI composite foam integrates the nanoscale pore structure of ZIF-8 and the micrometer-scale pore structure of PI, and utilizes the synergistic effect between the multi-level pore structures to provide abundant reaction sites and gas transmission channels for hydrate formation, thereby enhancing the adsorption and hydration gas storage performance of nanoporous materials. The composite product has a large specific surface area, good methane adsorption capacity and its strengthening effect on hydrate formation. At the same time, by achieving the synergistic effect between micro- and nano-pores, it promotes the rapid generation of natural gas hydrates.
[0028] (2) The metal organic framework ZIF-8 / polyimide foam material prepared by the present invention adopts a vacuum freeze drying method to load the metal organic framework material on the surface of the polyimide foam, thereby avoiding damage to the polyimide foam skeleton, while the porous structure will not be blocked, and the stability between the two is excellent;
[0029] (3) Compared with powder materials, the metal organic framework ZIF-8 / polyimide foam material prepared in the present invention is more convenient to recycle and can be recycled in the hydrate formation-decomposition process.
[0030] (4) The preparation method of the metal organic framework ZIF-8 / polyimide foam material of the present invention has low cost, simple process, high recyclability, environmentally friendly preparation, broad application prospects, and provides a feasible solution for the rapid generation of natural gas hydrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 and Figure 2 is a SEM image of the ZIF-8 / PI foam composite material prepared in Example 1 of the present invention;
[0032] Figure 3 1 is the TGA graph of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0033] Figure 4 FTIR graphs of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0034] Figure 5 is the XRD diagram of the ZIF-8 / PI foam composite material prepared in Example 1 and Example 1 of the present invention;
[0035] Figure 6 1 is the performance curve of Example 1, Comparative Example 3 and Comparative Example 4 during the hydrate formation process of the present invention;
[0036] Figure 7 1 is the performance curve of Example 1, Comparative Example 1 and Comparative Example 2 during the hydrate formation process of the present invention;
[0037] Figure 8 is a cycle performance curve of the ZIF-8 / PI composite foam material prepared in Example 4 of the present invention during the hydrate formation process;
[0038] Fig. 9 This is a physical picture of the ZIF-8 / PI composite foam material used for hydrate experiment in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The principles and features of the present invention are described below. The examples given are only used to explain the present invention but not to limit the scope of the present invention.
[0040] Example 1
[0041] The ZIF-8 / PI foam composite material prepared in this embodiment, wherein the mass ratio of ZIF-8:PI is 2:1, and the preparation method thereof comprises the following steps:
[0042] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0043] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 1 part of dibutyltin dilaurate, 10 parts of triethanolamine, and 280 parts of isocyanate.
[0044] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:2, and then high-temperature curing is performed at 180° C. for 3 hours to obtain a polyimide foam material.
[0045] 3) Weigh 2.67 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is referred to as solution C; weigh 2.94 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is referred to as solution D; quickly pour solution C into solution D, and stir to obtain solution E, i.e., a precursor solution of the metal organic framework ZIF-8.
[0046] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C for 24 hours to obtain a ZIF-8 / PI foam composite material.
[0047] Example 2
[0048] The ZIF-8 / PI foam composite material prepared in this embodiment, wherein the mass ratio of ZIF-8:PI is 1:1, the preparation method thereof comprises the following steps:
[0049] 1) 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 70°C for 3 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride was 4:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride to alcohols was 1.2:2.
[0050] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 50 parts of polyethylene glycol, 50 parts of water-soluble silicone oil, 5 parts of dibutyltin dilaurate, 20 parts of triethanolamine, and 300 parts of isocyanate.
[0051] 2) Solution A and Solution B are mixed in a mass ratio of 3:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:1, and then high-temperature curing is performed at 240° C. for 5 hours to obtain a polyimide foam material.
[0052] 3) Weigh 1.78 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is called solution C; weigh 1.96 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is called solution D; quickly pour solution C into solution D, and stir to obtain solution E, i.e., the precursor solution of the metal organic framework ZIF-8.
[0053] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C and 100 Pa for 24 h to obtain a ZIF-8 / PI foam composite material.
[0054] Example 3
[0055] The ZIF-8 / PI foam composite material prepared in this embodiment, wherein the mass ratio of ZIF-8:PI is 2.5:1, the preparation method thereof comprises the following steps:
[0056] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 4.5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0057] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 3 parts of dibutyltin dilaurate, 20 parts of triethanolamine, and 280-300 parts of isocyanate.
[0058] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:1, and then high-temperature curing is performed at 200° C. for 3 hours to obtain a polyimide foam material.
[0059] 3) Weigh 3.56 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is recorded as solution C. Weigh 3.92 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is recorded as solution D. Quickly pour solution C into solution D, stir and mix to obtain solution E, i.e., metal organic framework ZIF-8 solution.
[0060] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C and 100 Pa for 24 h to obtain a ZIF-8 / PI foam composite material.
[0061] Comparative Example 1
[0062] This comparative example uses a polyimide foam material, and its preparation method is the same as step 1) and step 2) of Example 1, specifically comprising the following steps:
[0063] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0064] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 1 part of dibutyltin dilaurate, 10 parts of triethanolamine, and 280 parts of isocyanate.
[0065] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:2, and then high-temperature curing is performed at 180° C. for 3 hours to obtain a polyimide foam material.
[0066] Comparative Example 2
[0067] This comparative example uses a metal organic framework ZIF-8, and its precursor solution is the same as step 3) of Example 1, specifically comprising the following steps:
[0068] 2.67 g of zinc nitrate hexahydrate was dissolved in 20 ml of methanol, recorded as solution C, and 2.94 g of 2-methylimidazole was dissolved in 20 ml of methanol, recorded as solution D; solution C was quickly poured into solution D, and the mixture was stirred to obtain solution E, i.e., the precursor solution of the metal organic framework ZIF-8.
[0069] In addition, the precursor solution of the metal organic framework ZIF-8 was allowed to react for 24 hours, and the ZIF-8 powder was separated; after washing with deionized water, the metal organic framework ZIF-8 powder was obtained by drying.
[0070] Comparative Example 3
[0071] This comparative example is a prepared ZIF-8 / PI foam composite material, wherein the mass ratio of ZIF-8:PI is 2:3, and the preparation method thereof is:
[0072] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0073] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 1 part of dibutyltin dilaurate, 10 parts of triethanolamine, and 280 parts of isocyanate.
[0074] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; wherein the mass ratio of water to isocyanate is 1:2, and then high-temperature curing is performed at 180° C. for 3 hours to obtain a polyimide foam material;
[0075] 3) Weigh 0.89 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is referred to as solution C; weigh 0.98 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is referred to as solution D; quickly pour solution C into solution D, and stir to mix to obtain solution E; in this step, the concentration of ZIF-8 in solution E is regulated by adjusting the concentrations of zinc nitrate hexahydrate and 2-methylimidazole.
[0076] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C and 100 Pa for 24 h to obtain a ZIF-8 / PI foam composite material.
[0077] Comparative Example 4
[0078] This comparative example is a prepared ZIF-8 / PI foam composite material, wherein the mass ratio of ZIF-8:PI is 10:3, and the preparation method thereof is:
[0079] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0080] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 1 part of dibutyltin dilaurate, 10 parts of triethanolamine, and 280 parts of isocyanate.
[0081] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:2, and then high-temperature curing is performed at 180° C. for 3 hours to obtain a polyimide foam material.
[0082] 3) Weigh 4.005 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is recorded as solution C; weigh 4.41 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is recorded as solution D; quickly pour solution C into solution D, stir and mix to obtain solution E; in this step, the concentration of ZIF-8 in solution E is controlled by adjusting the concentrations of zinc nitrate hexahydrate and 2-methylimidazole.
[0083] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C and 100 Pa for 24 hours to obtain a ZIF-8 / PI foam composite material.
[0084] Comparative Example 5
[0085] This comparative example is a prepared ZIF-8 / PI foam composite material, wherein the mass ratio of ZIF-8:PI is 3:1, and the preparation method thereof is:
[0086] 1) 3,3',4,4'-benzophenone tetracarboxylic dianhydride was dissolved in N,N-dimethylformamide, methanol was added thereto, the temperature was raised and stirred, and an esterification reaction was carried out at 60°C for 2 hours to obtain a carboxylate ester solution, which was naturally cooled to room temperature to obtain a solution A. The mass ratio of N,N-dimethylformamide to 3,3',4,4'-benzophenone tetracarboxylic dianhydride was 5:3, and the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol was 1:2.
[0087] Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and stirred after ultrasonic treatment to obtain solution B; the weight proportions of the components in solution B are: 40 parts of polyethylene glycol, 40 parts of water-soluble silicone oil, 1 part of dibutyltin dilaurate, 10 parts of triethanolamine, and 280 parts of isocyanate.
[0088] 2) Solution A and Solution B are mixed in a mass ratio of 2:1, water is added and stirred, and then poured into a mold for foaming; the mass ratio of water to isocyanate is 1:2, and then high-temperature curing is performed at 180° C. for 3 hours to obtain a polyimide foam material.
[0089] 3) Weigh 4.45 g of zinc nitrate hexahydrate and dissolve it in 20 ml of methanol, which is recorded as solution C; weigh 4.90 g of 2-methylimidazole and dissolve it in 20 ml of methanol, which is recorded as solution D; quickly pour solution C into solution D, stir and mix to obtain solution E; in this step, the concentration of ZIF-8 in solution E is regulated by adjusting the concentrations of zinc nitrate hexahydrate and 2-methylimidazole.
[0090] 4) Take 0.3 g of the polyimide foam material obtained in step 2) and 40 mL of solution E obtained in step 3) as raw materials, extract the gas in the polyimide foam material, then absorb solution E to saturation, let it stand for reaction and then take it out, wash it with deionized water, and vacuum freeze-dry it at -60°C and 100 Pa for 24 hours to obtain a ZIF-8 / PI foam composite material.
[0091] test:
[0092] The materials of the above-mentioned embodiment and comparative example are used for the rapid formation of natural gas hydrates, and the steps are as follows:
[0093] 1) Extract the gas from the material to be tested, then absorb water until saturated, and take out the material;
[0094] 2) Put the water-absorbed material into a high-pressure methane reactor, seal it and place it in a low-temperature constant temperature tank;
[0095] 3) When the temperature is constant at 1°C ± 0.2°C, open the methane cylinder to inflate the high-pressure reactor. After completion, close the methane cylinder, the hydrate reaction begins, and natural gas hydrate is generated.
[0096] Among them, the gas storage multiple of methane hydrate is defined as the STP volume of methane stored per unit volume of hydrate. The calculation formula for the gas storage multiple of methane hydrate at time t is:
[0097]
[0098] Where P0, V0, and T0 are the pressure, gas volume, and temperature at the initial moment, respectively. t 、T t are the pressure and temperature at any time of the reaction; N represents the amount of methane consumed at time t; N0 is the amount of methane at time 0; V mg is the molar volume of the gas; V w is the initial volume of the reaction solution, V mw is the molar volume of the reaction solution. R is the universal gas constant; Z is the compressibility factor; ΔV is the difference in molar volumes between water and methane hydrate, which is equal to 4.6 cm 3 / mol water. The test data are shown in Table 1.
[0099] Example 4
[0100] In addition, the same sample prepared in Example 1 was used to carry out the hydrate experiment in the above steps. After each experiment, the equipment was disassembled, the sample was taken out, washed with deionized water three times, and dried in a constant temperature oven. Then, the material was subjected to three natural gas hydrate formation experiments, which were marked as Example 4-1, Example 4-2, and Example 4-3, respectively.
[0101] Table 1
[0102]
[0103]
[0104] Figure 1 It shows that ZIF-8 / PI foam composites have rich micron-pore structure. Figure 2It shows that dense ZIF-8 nanomaterials are uniformly loaded on the PI skeleton, and these ZIF-8 materials present a regular dodecahedral structure morphology.
[0105] It can be seen from the data in Table 1 that Comparative Example 1 uses only polyimide foam material with a gas storage multiple of 20 V / V, and Comparative Example 2 uses only ZIF-8 powder, and no natural gas hydrate is generated; while the ZIF-8 / PI foam composite materials in Examples 1-3 of the present invention can effectively promote the formation of hydrates, and their gas storage multiples are as high as 98-103 V / V.
[0106] Compared with comparative examples 3, 4, and 5, the loading amount of ZIF-8 on PI foam in Examples 1-3 of the present invention has a significant effect on hydrate formation. In particular, the mass ratio of ZIF-8 to PI in the composite foam material prepared by the present invention is 1-2.5:1, which can achieve excellent hydrated gas storage performance. The inventor speculates that the reason may be that the amount of ZIF-8 loaded on PI in the material prepared in comparative example 3 is relatively low, and the main PI foam cannot be evenly covered, and the ZIF-8 adsorption-hydration composite gas storage effect cannot be brought into play to the best, while the excessive loading of ZIF-8 in the composite foam material prepared in comparative examples 4 and 5 will cause the pores in the PI material to be blocked, which is not conducive to gas-liquid contact and reduces the hydrate gas storage capacity.
[0107] From the data of Examples 4-1, 4-2 and 4-3, it can be seen that after multiple cycles of use, the hydration gas storage multiple of the composite material prepared by the present invention is maintained within a reasonable range of 95-105 v / v, indicating that the composite material has excellent cyclic use. Fig. 9 The final product of the present invention is shown to be sponge-like, which solves the problem that conventional ZIF-8 powder is difficult to recycle.
Claims
1. A method for preparing a metal organic framework ZIF-8 / polyimide foam material, characterized in that: Using a polyimide foam material and a precursor solution of a metal organic framework ZIF-8 as raw materials, extracting the gas in the polyimide foam material, then absorbing the precursor solution of the metal organic framework ZIF-8 until saturated, taking it out after standing for reaction, washing it with deionized water, and vacuum freeze-drying it to obtain a metal organic framework ZIF-8 / polyimide foam material, namely, a ZIF-8 / PI foam composite material; The amount or concentration of the ZIF-8 precursor solution is controlled so that the mass ratio of ZIF-8 to PI in the final foam material is 1-2.5:1; The preparation process of the polyimide foam material is as follows: 1) dissolving 3,3',4,4'-benzophenone tetracarboxylic dianhydride in a solvent, adding alcohol thereto, heating and stirring, carrying out esterification reaction to obtain a carboxylate solution, and naturally cooling to room temperature to obtain a solution A; Polyethylene glycol, water-soluble silicone oil, dibutyltin dilaurate, triethanolamine and isocyanate are mixed, and after ultrasonic treatment, the mixture is stirred to obtain a solution B; 2) Solution A and solution B are mixed, water is added and stirred, and then poured into a mold for foaming, and then high-temperature curing is performed to obtain a polyimide foam material.
2. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: The preparation process of the precursor solution of the metal organic framework ZIF-8 is as follows: Weigh zinc nitrate hexahydrate and dissolve it in a solvent, which is called solution C; weigh 2-methylimidazole and dissolve it in a solvent, which is called solution D; The C solution is quickly poured into the D solution, and the mixture is stirred to obtain a precursor solution of the metal organic framework ZIF-8.
3. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: In step 1), the solvent is N,N-dimethylformamide and the alcohol is methanol; the mass ratio of the solvent to 3,3',4,4'-benzophenone tetracarboxylic dianhydride is 4:3-5:3; the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic dianhydride to alcohol is 1:2-1.2:
2.
4. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: In step 1), the esterification reaction temperature is 60-70° C., and the esterification reaction time is 2-3 h.
5. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: In step 1), the weight proportions of the components in solution B are: 40-50 parts of polyethylene glycol, 40-50 parts of water-soluble silicone oil, 1-5 parts of dibutyltin dilaurate, 10-20 parts of triethanolamine, and 280-300 parts of isocyanate.
6. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: In step 2), the mass ratio of solution A to solution B is 2:1-3:1; the mass ratio of added water to isocyanate is 1:2-1:
1.
7. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 1, characterized in that: In step 2), the high temperature curing temperature is 180-240° C. and the time is 3-5 hours.
8. The method for preparing the metal organic framework ZIF-8 / polyimide foam material according to claim 2, characterized in that: In step 2), the solvents of solution C and solution D are both methanol.
9. An application of the metal organic framework ZIF-8 / polyimide foam material according to any one of claims 1 to 8, characterized in that: For the rapid generation of natural gas hydrates, the steps are: 1) extracting gas from the ZIF-8 / PI foam composite material, then absorbing water until saturated, and taking out the ZIF-8 / PI foam composite material; 2) placing the water-absorbed ZIF-8 / PI foam composite material into a high-pressure methane reactor, sealing it and placing it in a low-temperature constant temperature tank; 3) When the temperature is constant at 1°C ± 0.2°C, open the methane cylinder to inflate the high-pressure reactor. After completion, close the methane cylinder, the hydrate reaction begins, and natural gas hydrate is generated.